Deposits Mobilization by Baroda District Central Co-Operative Bank Ltd. (A Cooperative Bank of Gujarat) - Kablana, Anand Singh; Kumar, Vikas; Kumar, Shelindar (Indian Journal of Finance, 2011)
Agriculture plays a dominant role in the Indian Economy, providing employment for 70 percent of the people and contributing 42 percent to the Gross National Product (GNP). Agriculture has been and will continue to be the life line of the Indian economy. Agriculture is affected by several factors. Credit is one of the major factors affecting the agricultural development. There are two source of agriculture - credit first is "Non-institutional and Secondly is Institutional". The first action was taken by the "British Government" in context of institutional credit for the agriculture sector. The second step was taken in 1904 in context of institutional loans for agriculture as a co-operative movement. The Co-operative Societies Act, 1904, was introduced on the recommendation of the Law Committee appointed by the Government of India, under the chairmanship of "Edward Law". There are three objectives of the present study, firstly is to study the growth of Deposit, Second is to review the pattern of deposit mobilizations and thirdly, is to offer suggestions for improving the performance of the study unit -Baroda Central Co-operative Bank Ltd.